Representation of Male Roles and Characters in Indonesian Classic dangdut Songs From the 1970s to the 1990s - Tirza Marshanda Hartono; Chafit Ulya (Universitas Muhammadiyah Malang, 2025)
This research was motivated by the lack of comprehensive research on the representation of masculinity in classic Indonesian dangdut songs from the 1970s, 1980s, and 1990s. These songs contain authentic social constructions of male roles and characters in society, but have not been analyzed in depth using masculinity theory. This study aims to identify and analyze how male masculinity is represented in the lyrics of classic dangdut songs through the seven dimensions of masculinity proposed by Janet Saltzman Chafetz, namely physical, functional, sexual, emotional, intellectual, interpersonal, and personal characteristics. This study uses a qualitative descriptive method with a critical discourse analysis approach. The results show that masculinity is presented in a multidimensional way: physically strong and tough; responsible as a breadwinner and leader; subtly expressing sexual interest; reflecting emotions such as regret and sadness; thinking logically and wisely; maintaining relationships with responsibility and maturity; and adhering to spiritual values and principles of life. These findings confirm that masculinity in classic dangdut songs is not merely synonymous with dominance, but also reflects the emotional, rational, and spiritual sides of men in Indonesian popular culture.